1011. LAUNAEA CERVICORNIS: Compositae. (21st January 2022) - Hind, Nicholas; Moore, Richard; King, Christabel
Summary: Launaea cervicornis (Boiss.) Font Quer & Rothm. (Compositae: Lactuceae: Hyoseridinae) is illustrated and described. The species is endemic to the Balearics, and is the dominant species in the limestone cliff‐top plant association Launaeion cervicornis (O. Bolòs & Vigo ex Y. Gil & Llorens) Rivas‐Martínez, Fernández‐González & Loidi) on the islands. Notes on cultivation, propagation, pests and diseases and availability are provided. The position of Launaea Cass. in the tribe Lactuceae (= Cichorieae) subtribe Hyoseridinae Less. is discussed, as is the position of the species within the genus, as the sole taxon in Launaea sect. Cervicornes N. Kilian. The reproductive biology of the species is discussed. The species exhibits a particularly short flowering time (per floret) and flowering period, maximizing on calm periods and an abundance of flower visitors/pollinators. The plant possesses three different dispersal mechanisms – anemochory (for solitary achenes), and atelechory and barochory for mature, unopened involucres. The former ensuring there is some movement away from the parent plant, and the latter two effectively ensuring that propagules are not instantly blown off the cliffs into the sea.